2013
DOI: 10.1128/iai.00345-13
|View full text |Cite|
|
Sign up to set email alerts
|

The RNA Chaperone Hfq Is Required for Virulence of Bordetella pertussis

Abstract: bBordetella pertussis is a Gram-negative pathogen causing the human respiratory disease called pertussis or whooping cough. Here we examined the role of the RNA chaperone Hfq in B. pertussis virulence. Hfq mediates interactions between small regulatory RNAs and their mRNA targets and thus plays an important role in posttranscriptional regulation of many cellular processes in bacteria, including production of virulence factors. We characterized an hfq deletion mutant (⌬hfq) of B. pertussis 18323 and show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 66 publications
3
41
1
Order By: Relevance
“…How or why is more ACT translated and secreted in the rseA mutant? Bibova et al showed that in the absence of the RNA chaperone Hfq, less ACT was produced, suggesting that a small RNA posttranscriptionally controls ACT translation (21). However, we did not observe differential expression of hfq in our RNA-seq analysis (Table S1).…”
Section: Figcontrasting
confidence: 50%
See 2 more Smart Citations
“…How or why is more ACT translated and secreted in the rseA mutant? Bibova et al showed that in the absence of the RNA chaperone Hfq, less ACT was produced, suggesting that a small RNA posttranscriptionally controls ACT translation (21). However, we did not observe differential expression of hfq in our RNA-seq analysis (Table S1).…”
Section: Figcontrasting
confidence: 50%
“…However, we did not observe differential expression of hfq in our RNA-seq analysis (Table S1). In the same study, it was observed that loss of hfq resulted in decreased pertussis toxin gene and protein expression (21). Due to these observations, it does not seem likely that hfq is responsible for the inverted pertussis-toxinto-ACT expression that we observe in the PM18 strain.…”
Section: Figsupporting
confidence: 48%
See 1 more Smart Citation
“…It may actively remodel the RNAs to melt inhibitory secondary structures and also may serve passively as a platform to allow sRNAs and mRNAs to sample potential complementarity (Waters and Storz, 2009). Besides, Hfq is frequently required to protect the sRNAs from cellular ribonucleases such as RNase E (Papenfort and Vanderpool, 2015), and for many intracellular and extracellular pathogens it is known that Hfq deficiency dramatically affects virulence and fitness ( Escherichia coli , Kulesus et al, 2008; V. alginolyticus , Deng et al, 2016; Klebsiella pneumoniae , Chiang et al, 2011; Pseudomonas aeruginosa , Sonnleitner et al, 2003; Bordetella Pertussis , Bibova et al, 2013). …”
Section: Classification Of Srnasmentioning
confidence: 99%
“…We now know that there are other pathways by which virulence is controlled in this genus (57)(58)(59)(60)(61), but how these pathways relate to one another and to Bvg is still to be fully determined. The Bvg system controls production of many bacterial proteins-importantly ACT and other virulence factorsand expression is downregulated in response to sulfate, nicotinic acid, and a shift to lower temperature (25°C).…”
Section: Discussionmentioning
confidence: 99%